Alpha-lactalbumin amyloid-like fibrils for intestinal delivery: Formation, physiochemical characterization, and digestive fate of capsaicin-loaded fibrils. (March 2023) - Romano, Alon; Engelberg, Yizhaq; Landau, Meytal; Lesmes, Uri
Abstract: Engineering protein architectures offers numerous opportunities to deliver consumers with added values yet mandates careful screening of possible risks. This study explores the fabrication of bovine alpha-lactalbumin (ALA) amyloid-like fibrils (AF) for gastro-intestinal delivery of capsaicin (CAP), a pungent compound which possesses health beneficial virtues. Acidic incubation of ALA with CAP accelerates formation of ALA-AF, as confirmed by transmission electron microscope, with a size increase from 3.7 ± 0.4 nm to 175 ± 58 nm and a melting temperature shift from T m = 61.8 °C to T m = 89.9 °C for native ALA and ALA-AF entrapping 200 μM CAP, respectively. In addition to encapsulation efficiency and loading capacity measurements, this work provides evidence that fibrillation attenuates the in vitro digestive proteolysis of ALA and diminishes the levels of bioaccessible bioactive peptides by an order of magnitude compared to native ALA. This is accompanied by sustained release of 7.8 ± 1.7% to 55.7 ± 12.3% CAP under gastric and intestinal conditions. Overall, this work presents a new possible avenue for designing protein structures to entrap bioactive moieties along-side a call to interrogate the possible ramifications to protein digestion and consumer health. Graphical abstract: Image 1 Highlights: Addition of capsaicin enhances the amyloid fibrillation of alpha-lactalbumin. Capsaicin increases colloidal and thermo-stability of α-lactalbumin fibrils. Encapsulation efficiency of capsaicin ranges between 85 ± 7 to 41 ± 11%. α-lactalbumin fibrils hinders gastric proteolysis and retains capsaicin release. Protein fibrillization reduces the abundancy of bioaccessible bioactive peptides.